Syzygium malaccense leaf extract-mediated silver nanoparticles: synthesis, characterization, and biomedical evaluation in Caenorhabditis elegans and lung cancer cell line - Santosh Mallikarjun Bhavi; Bothe Thokchom; Sapam Riches Singh; Sukesh Kumar Bajire; Rajesh P. Shastry; B. S. Srinath; Shivanand S. Bhat; Kotresha Dupadahalli; Chandramohan Govindasamy; Swati Ravi Chalekar; B. P. Harini; Ramesh Babu Yarajarla (Green Chemistry Letters and Reviews)
The study explores the green synthesis and characterization of silver nanoparticles using Syzygium malaccense (L.) Merr. & L. M. Perry leaf extract (SM-AgNPs). UV-Visible spectroscopy confirmed the reduction of silver ions, showing an absorption peak at 406 nm. X-ray Diffraction (XRD) analysis revealed a face centered cubic structure with an average particle size of 23.55 nm. Dynamic Light Scattering (DLS) and zeta potential analyses indicated a mean size of 40.1 nm and a surface charge of −40.1 mV. FTIR spectroscopy identified functional groups involved in nanoparticle stabilization, while Energy Dispersive X-ray (EDX) analysis confirmed silver content. Transmission Electron Microscopy (TEM) and Atomic Force Microscopy (AFM) provided detailed insights into particle morphology. Anticancer assays showed dose-dependent cytotoxicity against A549 cancer cells (LC50: 7.62 μg mL−1) with minimal effects on L-132 normal cells (LC50: 73.55 μg mL−1), highlighting selectivity. Additionally, SM-AgNPs increased Caenorhabditis elegans survival and reduced paralysis under pathogenic bacterial exposure. This study demonstrates the potential of SM-AgNPs in biomedical applications, emphasizing selective anticancer activity and antimicrobial effects in vivo.